Implementing strategic change a survey of British and German workers - Harding, Rebecca
Large manufacturing companies are developing strategies to respond to changing competitive circumstances. These commonly have their major focus on technology and human resource development through the implementation both of new technologies and of corresponding, quality centered, approaches to organization. There is a wide range of theoretical and empirical research evidence on the creation and espousal of these strategies, but, until recently, little on their implementation. This paper looks at the implementation of strategy in one company renowned for its strategic leadership, particularly in the area of new organizational methods of achieving manufacturing excellence through continuous improvement. Through an examination of its operations in two countries it is possible to highlight some of these key elements of successful implementation of organizational change. On the basis of this it argues that there are some important differences between the characteristics of the two workforces which have had a profound effect on the implementation of strategic change, and in particular on the degree to which a company is free to introduce change gradually. Such a survey points to the need for further comparative analyses of strategic change in two national environments similar to that undertaken here.
The study is based on a large manufacturing organization and examines its operations in both the UK and Germany. Key elements for successful organizational change are highlighted.
Keywords: Strategic change